2004
DOI: 10.1161/01.cir.0000133278.81226.c9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Erectile Dysfunction and Silent Myocardial Ischemia in Apparently Uncomplicated Type 2 Diabetic Patients

Abstract: Background-Erectile dysfunction (ED) is associated with coronary artery disease (CAD). In diabetic patients, CAD is often silent. Among diabetic patients with silent CAD, the prevalence of ED has never been evaluated. We investigated whether ED is associated with asymptomatic CAD in type 2 diabetic patients. Methods and Results-We evaluated the prevalence of ED in 133 uncomplicated diabetic men with angiographically verified silent CAD and in 127 diabetic men without myocardial ischemia at exercise ECG, 48-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(121 citation statements)
references
References 31 publications
(33 reference statements)
5
113
0
2
Order By: Relevance
“…15 Silent ischemia and ED are also known to occur in patients with uncomplicated diabetes. 16 These findings support the idea that ED and CAD share similar pathophysiological mechanisms and form a dangerous cycle.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…15 Silent ischemia and ED are also known to occur in patients with uncomplicated diabetes. 16 These findings support the idea that ED and CAD share similar pathophysiological mechanisms and form a dangerous cycle.…”
Section: Discussionsupporting
confidence: 70%
“…There is an association between the severity of CAD and ED. [12][13][14][15][16] Many researchers have reported that ED manifests approximately 24-36 months before the manifestation of CAD. 12 Previous studies reported that the existence ED is associated with a twofold increase in the risk of STEMI among men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Erectile dysfunction commonly occurs in the presence of silent CAD, 3,[18][19][20] with a time window between ED onset and a CAD event of 2 to 5 years (class Ia). 3,4,21 Furthermore, evidence suggests that ED is predictive of peripheral arterial disease (PAD) 22 and stroke.…”
Section: Sexual Inquiry Of All Menmentioning
confidence: 99%
“…In a study of patients with type 2 diabetes, ED was significantly more prevalent in men with silent CAD (33.8%) identified by EST than in those without silent CAD (4.7%). 18 Chemical stress tests (dipyridamole [Persantine, Boehringer Ingellheim GmbH, Ingelheim, Germany] or adenosine with nuclear imaging) are appropriate for patients who cannot complete an EST (eg, inability to exercise due to a disabling condition such as arthritis). If the baseline electrocardiogram makes EST unavailable or noninterpretable, the consensus panel recommends refer-ral to a cardiologist or a practice with cardiology expertise for further evaluation.…”
Section: Treatment Additional Cardiovascular Evaluation and Referralmentioning
confidence: 99%